Performance of stone mastic asphalt incorporating Kenaf fibre - Nur Syafiqah Shamimi, Mohd Zali (2019)
Stone Mastic Asphalt (SMA) contains a high amount of aggregate making it has a better interlocking due to the stone to stone contact but it is susceptible to binder drain down problems. Thus, the aim of this study is to utilize different percentages of Kenaf fibre in Stone Mastic Asphalt to overcome issues related to Stone Mastic Asphalt such as rutting and cracking due to high traffic volumes and extreme weather. Among the test involved were LA Abrasion, Marshall Stability, Resilient Modulus, and Dynamic Creep. From the results, it shows that the addition of 0.2% fibre contributes to lowest value of abrasion. While, 0.2% fibre produce the highest density. It could be seen 0.6% of Kenaf fibre producing highest value of resilient modulus. Dynamic creep also shows a significant value in 0.2% addition. Thus, it can be concluded that the existence of fibre is capable in enhancing the performance of SMA which is evident for instance, the density. For future study, it is recommended to analyses the performance of SMA in terms of creep resistance, Marshall Stability, and rutting resistance of SMA with the existence of Kenaf fibre in order to prove its reliability in various applications in asphaltic mixture.